Introducing 'riverconn': an R package to assess river connectivity indices. (October 2022) - Baldan, Damiano; Cunillera-Montcusí, David; Funk, Andrea; Hein, Thomas
Abstract: Fragmentation affects river ecosystems worldwide by dampening the movement and dispersal of aquatic organisms and material (such as sediment, water, nutrients) across the river network. In this paper, we develop river connectivity indices to explain biodiversity patterns, prioritize reaches that need habitat restoration and barriers that need improvement. We provide a general framework for calculating connectivity indices by disentangling the contribution of the river network's physical setup (structural connectivity) from the process-driven and biota-related contribution (functional connectivity). To facilitate the calculations, the R package 'riverconn' is introduced. A prioritization of habitats and barriers is carried out for the Ebro river (North-West Iberian Peninsula) using indices setups accounting for different classes of organisms and dispersal traits. Resulting prioritizations are very diverse. 'Riverconn' can support scientists and managers working on riverscape planning and population and community ecology by providing a means to compute and compare a wide array of fragmentation indices. Highlights: The R package 'riverconn' is introduced to calculate catchment and reach connectivity indices. Structural and functional connectivity are disentangled. Based on the formulation, connectivity indices and resulting habitats and barriers prioritization can be highly diverse. 'riverconn' can be used in planning conservation and connectivity improvement, population and community ecology.